Prevalence of sensitization to 'improver' enzymes in UK supermarket bakers. Issue 7 (2nd March 2016) - Jones, M.; Welch, J.; Turvey, J; Cannon, J.; Clark, P.; Szram, J.; Cullinan, P.
Abstract: Background: Supermarket bakers are exposed not only to flour and alpha‐amylase but also to other 'improver' enzymes, the nature of which is usually shrouded by commercial sensitivity. We aimed to determine the prevalence of sensitization to 'improver' enzymes in UK supermarket bakers. Methods: We examined the prevalence of sensitization to enzymes in 300 bakers, employed by one of two large supermarket bakeries, who had declared work‐related respiratory symptoms during routine health surveillance. Sensitization was determined using radioallergosorbent assay to eight individual enzymes contained in the specific 'improver' mix used by each supermarket. Results: The prevalence of sensitization to 'improver' enzymes ranged from 5% to 15%. Sensitization was far more likely if the baker was sensitized also to either flour or alpha‐amylase. The prevalence of sensitization to an 'improver' enzyme did not appear to be related to the concentration of that enzyme in the mix. Conclusions: We report substantial rates of sensitization to enzymes other than alpha‐amylase in UK supermarket bakers; in only a small proportion of bakers was there evidence of sensitization to 'improver mix' enzymes without sensitization to either alpha‐amylase or flour. The clinical significance of these findings needs further investigation, but our findings indicate that specific sensitization in symptomatic bakers may not be identified without consideration of a wide range of workplace antigens.